2003
DOI: 10.1152/ajpcell.00267.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin-1 enhances barrier function in T84 epithelia through PKC-dependent regulation of tight junction proteins

Abstract: Protein kinase C (PKC) is known to regulate epithelial barrier function. However, the effect of specific PKC isozymes, and their mechanism of action, are largely unknown. We determined that the nonphorbol ester PKC agonist bryostatin-1 increased transepithelial electrical resistance (TER), a marker of barrier function, in confluent T84 epithelia. Bryostatin-1, which has been shown to selectively activate PKC-alpha, -epsilon, and -delta (34), was associated with a shift in the subcellular distribution of the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…(i) Representative blot occludin in the maintenance of a functioning tight junction complex, and evidence suggests that it is the claudin proteins that play a pivotal role in the regulation of tight junctions. After exposure to CsA, increased expression of claudin-1 and claudin-3 was observed, both of which are implicated in the maintenance of tight junction integrity (32)(33)(34) No alterations in claudin-2 expression were detected after CsA treatment. Claudin-2 is associated with increased "leakiness" across epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…(i) Representative blot occludin in the maintenance of a functioning tight junction complex, and evidence suggests that it is the claudin proteins that play a pivotal role in the regulation of tight junctions. After exposure to CsA, increased expression of claudin-1 and claudin-3 was observed, both of which are implicated in the maintenance of tight junction integrity (32)(33)(34) No alterations in claudin-2 expression were detected after CsA treatment. Claudin-2 is associated with increased "leakiness" across epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…Claudin-1-deficient mice manifest a severely compromised epidermal barrier and die within 24 h of birth due to dehydration (62). Furthermore, bryostatin-1-induced tightness of the TJs correlates with enhanced membrane association of claudin-1 in T84 epithelial cells (48). Overexpression of claudin-4 has been shown to increase TER in MDCK II cells (49), and a recent study describing segmental distribution of various claudins in the mouse nephron showed that claudin-3 and -4 are expressed mainly in the "tight" epithelia of the kidney and that only claudin-1, -3, -4, and -8 are expressed in the collecting segment of the kidney nephron (60), the segment with the highest TER.…”
Section: Discussionmentioning
confidence: 99%
“…EGF Induces Intracellular Redistribution and Increases Protein Synthesis of Claudin-1-Overexpression of claudin-1 has been shown to increase TER and the number of TJ strands in MDCK II cells (46,47), and bryostatin-1-induced TJ tightness in T84 epithelial cells correlates with enhanced membrane association of claudin-1 (48). In this study, in contrast to claudin-2, EGF treatment induced significant increases in claudin-1 expression selectively in the detergent-insoluble fractions within 1 h after EGF treatment, and claudin-1 expression was 213 and 233% of the control values after 8 and 18 h of EGF treatment, respectively (Fig.…”
Section: Fig 1 Effect Of Egf On Ter In Mdck II Cellsmentioning
confidence: 99%
“…This is consistent with the data from skin. 24 As the functional TJ proteins are insoluble in nonionic detergent, 10,12,29,30 in the present study, proteins from ALIcultured cells were divided into nonionic detergent (NP-40)-soluble and -insoluble fractions, and the level of claudin-1 and claudin-4 in each fraction then measured. Claudin-4 levels were lower in pH 2-stimulated cells compared with control conditions, in a time-dependent manner, suggesting that acid stimulation delocalized the claudin-4 from the TJs in the superficial layers.…”
Section: Squamous Epithelial Barrier Function T Oshima Et Almentioning
confidence: 99%